2018
DOI: 10.1016/j.partic.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency–amplitude behavior in the incipient movement of grains under vibration

Abstract: This paper focus on the onset of the movement of particles placed on a horizontal rough surface subjected to a vertical sinusoidal vibration. We track the problem through experiments, theory and numerical simulations. The frequencies needed to put particles in movement decays exponentially with the input amplitude of the oscillations. This behavior is explained through a simple approach where a forced damped harmonic oscillator is used with a spring constant representing all the interactions between the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The exponential behavior found here is in agreement with the one reported in [13] and the range of values for the frequencies is again quite lower than that derived from the elastic properties of the materials involved [1,2].…”
Section: Experimental Set Up and Proceduressupporting
confidence: 90%
See 1 more Smart Citation
“…The exponential behavior found here is in agreement with the one reported in [13] and the range of values for the frequencies is again quite lower than that derived from the elastic properties of the materials involved [1,2].…”
Section: Experimental Set Up and Proceduressupporting
confidence: 90%
“…In a previous work [13], it has been shown that the critical frequencies needed to destabilize a particle on a vertically vibrated surface decay exponentially with the amplitude of the oscillation and that the frequencies were much lower than those related to the elastic properties of the material constituting the particles.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, authors found that the stiffness of a spherical particle is not constant but increases with particle deformation [14]. Here, the critical acceleration for detachment decreases as A increases [55], so does the deformation of the particle. Thus, it is expected that k (so  0 ) decreases with A.…”
Section: Theoretical Approachmentioning
confidence: 93%
“…In this section, the main findings for the movement initiation of individual particles placed on a horizontal rough surface subject to a vertical sinusoidal vibration are presented as a result of a series of experiments, theoretical analysis, and numerical simulations performed in our work group in the last years [55,56]. The aim here is to determine the critical frequencyamplitude values of the vibration necessary to start the movement of at least half of the particles on the surface.…”
Section: Destabilization Of Grains By Vibrationmentioning
confidence: 99%
See 1 more Smart Citation